Alternatywny system obrotu w Polsce - pierwsze miesiące funkcjonowania - Pauka, Marek (Alternative Investment Market in Poland - the First Months, 2008)
The first two months of running were a hard step but a steady development for The New Connect, Polish AIM. Although negative moods in the market, next companies start issuing new shares using this platform. The paper presents results of research about this alternative market for issuers and potential investors. The New Connect has become relatively cheap way to obtain capital and to achieve the company's credibility in the financial market, but low liquidity may be a problem for the right valuation of the firm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 426-431